Penurunan Perilaku Membolos Siswa melalui Pendekatan Konseling Singkat Berfokus Solusi - Ratnawati Wahyuningsih, Dwi; Purwoko, Budi; All Habsyi, Bakhruddin (UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to explore the effectiveness of Solution-Focused Brief Counseling (SFBC) in reducing student truancy behavior. Employing a guidance and counseling action research methodology, the research involved three 11th-grade students identified with habitual truancy. The SFBC approach emphasizes problem resolution by identifying precise solutions tailored to students' challenges. The study was conducted over two cycles, each comprising four stages: planning, implementation of SFBC, observation, and reflection. In the first cycle, a reduction in truancy was observed: student A decreased from 7 to 4 instances, student B from 4 to 2, and student C from 5 to 3. The second cycle demonstrated a more significant decline: student A from 4 to 1, student B from 2 to 0, and student C from 3 to 1. These findings suggest that SFBC is an effective intervention for mitigating truancy among students.